Simulation of the Effect of Chilling Injury and Nitrogen Supply on Floret Fertility and Yield in Rice - Godwin, DC; Meyer, WS; Singh, U. (Commonwealth Scientific and Industrial Research Organisation, 1994)
Evidence exists that night temperatures <18C immediately preceding flowering in rice crops can adversely affect floret fertility and, hence, yields. It has been suggested that sterility induced by low temperature is also influenced by floodwater depth and nitrogen (N) rate. In southern New South Wales, low night-time temperatures are believed to be a major constraint to the achievement of consistently high yields. The availability of a comprehensive model of rice growth and yield that is sensitive to this constraint would aid the development of better management practices. CERES RICE is a comprehensive model that simulates the phasic development of a rice crop, the growth of its leaves, stems, roots, and panicles, and their response to weather. It also simulates the water and N balances of the crop and the effects of stresses of water and N on the yield-forming processes. The model has been extensively tested in many rice-growing systems in both tropical and temperate environments. However, the original model was unable to simulate the level of chilling injury evident from yield data from southern New South Wales. This paper reports modifications made in the model to simulate these effects and the evaluation of the model in environments of low night temperature. Inclusion of the chilling injury effect greatly improved the accuracy of estimated yields from treatments in an extensive field experiment. However, additional testing with a wider range of data sets is needed to confirm the international applicability of the modifications.